Analysis and Evaluation of Market and Financial Risks in Small and Medium-Sized Enterprises - Maria Hudakova; Jan Dvorsky; Katarina Buganova; Ludmila Kozubikova (Communications - Scientific letters of the University of Zilina, 2018)
The essence of the article is based on the collected and processed data from the survey to analyze, assess and evaluate the impact of the factor, which is the number of employees, on the market and financial risks, identified by managers of the SMEs in the Zilina region of Slovakia. The analysis of market and financial risks is carried out through the analysis of the selected statistical characteristics, using the point and interval estimates and methods of mathematical statistics. Interval estimation enables to determine not only the best estimate, but the entire interval with a certain probability of possible estimates of the mean value of the market and financial risks of a basic file, since the managers of an enterprise are more interested in intervals than in a point value. Results of the survey showed that the number of employees has an impact on the mean value of the market and financial risks of the SMEs in the Zilina region and therefore it is not possible to underestimate it.